Fluorescence Quenching of b-Casein by Silver Nanoparticles and Copper Nanoparticles in Presence of Sugars: A Quantitative Exploration - Vasumathi, V.; Santhanalakshmi, J. (Asian Journal of Chemistry, 2017)
The protein b-casein (BCA) exhibits a strong fluorescence emission, which is sensitive to active quenchers. Metal nanoparticles like copper nanoparticles and silver nanoparticles with enhanced and unique properties are reported to quench protein fluorescence appreciably. In the present work, the fluorescence quenching effects of metal nanoparticles on the protein fluorescence are extensively studied in presence of various sugar molecules. This may play a significant role in the sensing applications of sugar molecular systems in the presence of metal nanoparticles. b-Casein is used as fluorophore and sugar molecular systems like sucrose, maltose, fructose, lactose, galactose and glucose are chosen as quenchers and the protein-sugar interactions are arrived from fluorescence quenching results in the presence of copper nanoparticles and silver nanoparticles. To find the role of life time on the intensity of fluorescence, time resolved fluorescence measurements for the protein-sugar systems in the presence and absence of nanoparticles is measured. The protein-nanoparticles-sugar fluorescence interactions are analyzed by using Stern-Volmer plots and thermodynamic plots using fluorescence intensity quenching data. The trends in the extent of quenching action on protein fluorescence and also the binding interactions among protein sugar systems are quantified in the presence of copper nanoparticles and silver nanoparticles separately, in terms of Stern-Volmer constant values and binding constants values. b-Casein is found to interact strongly with the quenchers in the presence of copper nanoparticle and silver nanoparticle. Silver nanoparticle is read to be a better quenching mediator than copper nanoparticle for the fluorescence intensity in molecular interactions. Order of sugars quenching the protein fluorescence in presence of the nanoparticles is found.